Analysis of Macroeconomi Factor Effect on the Stock Price Index in Jakarta Islamic Index - Miftahul Huda; Ahmad Suminto; Amelia Septiyani; Muhammad Nabil Hanif (Dialektika: Jurnal Ekonomi dan Ilmu Sosial)
The country’s economy slowdown causes the affected exchange rate or exchange rate to weaken, and Bank Indonesia’s interest rate policy at the time of the economic downturn decreases, it has an impact on the stock index in the JII.